Test Activities Antibakteriekstrak Ethanol Young And Old Leaves Of The Soursop(Annonamuricata L.) Against Staphylococcus aureus - Sari, Dwi Latifah; Sudarmi, Sudarmi; Patilaya, Popi (Talenta Conference Series: Science and Technology (ST), 2018)
Soursop (Annona muricata L.) has been used for generations by some communities in Indonesia to treat diseases. Soursop leaves are used as an alternative treatment for cancer, by boiling them in the water and consuming it. In addition to the treatment of cancer, soursop plant is also used for the treatment of skin diseases such as boils. This study aimed to determine the antibacterial activity of ethanol extract of soursop leaves of young and old against Staphylococcus aureus, determine the content of secondary metabolites, and find out the diameter of inhibitory young leaves and old leaves of soursop in inhibiting Staphylococcus aureus. Soursop leaves were extracted by maceration using ethanol 96%. The extract obtained was then carried out to phytochemical screening. Antibacterial activity test was conducted using disc the Kirby-Bauerdiffusion. This study used 6 concentrations of 500 mg/mL, 400 mg/mL, 300 mg/mL, 200 mg/mL, 100 mg/mL, 80 mg/mL, 60 mg/mL, 40 mg/mL, 20 mg/mL, 10 mg/mL and 1 mg/mL. A positive control used soursop leaf extract of young and old while a negative one used DMSO 10%. Based on phytochemical screening, ethanol extract of soursop leaves contained alkaloids, flavonoids, saponins, tannins, steroids/triterpenoids and glycosides. The antibacterial activity of ethanol extract of leaves of young soursop was higher in inhibitory diameter than the ethanol extract of old soursop leaves. It could be seen that a concentration of 500 mg/mL was equal to 10.87 mm and 8.68 mm; a concentration of 400 mg/mL was equal to 9.15 mm and 7.3 mm; a concentration of 300 mg/mL was equal to 8.34 mm and 6.30 mm; a concentration of 200 mg/mL was equal to 8.23 mm and 7.08 mm; a concentration of 100 mg/mL was equal to 6.32 mm and 6.18 mm, and a concentration of 80 mg/mL did not leave a diameter inhibitory to bacteria Staphylococcus aureus. Young soursop leaf ethanol extract was more effective than the old soursop one against Staphylococcus aureus.